ANALISIS PELESTARIAN CAGAR BUDAYA STUDI KASUS CAGAR BUDAYA TAMAN SARI GUNONGAN - Eva Sulastri Sagita; Nurlaili Nurlaili; Nurkamari Nurkamari (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM) Universitas Jabal Ghafur, 2022)
This study aims to analyze the preservation of the Taman Sari Gunongan cultural heritage site in the city of Banda Aceh. This study used a qualitative research design with a descriptive type of research. The data sources used are primary data sources and secondary data sources. There are three data collection techniques in this study, namely interviews, observation, and documentation. The results of this study indicate that the Taman Sari Gunongan site is managed well by the tourism office of the city of Banda Aceh. In preserving the park, archaeologists, historians, BPCB (Balai Pemestarian Cagar Budaya), the government and the local community have a very important role in preserving the history of The Taman Sari Gunongan cultural heritage before and after being designated as a cultural heritage.Keywords: Preservation of cultural heritage, Taman Sari Gunongan site, the role of the government